Developing Textbook by Using Reading Strategic Based Instruction Method for Shariah Economy Department: Pengembangan Buku Ajar dengan Menggunakan Metode Reading Strategic Based Instruction Jurusan Ekonomi Syariah - Afidah, Nurul; Hanifah, Hanifah (JEES (Journal of English Educators Society), 2018)
This research aims at developing reading textbook for Shariah Economy students of the first year. The strategy applied on the textbook was RSBI (Reading Strategy Based Instruction). In this study, the researcher adapted some steps of research and development that was invented by Borg and Gall. The steps in this research covered need analysis, products development, expert validation, revison, try out, and revision. The final Products of this study is reading material that is developed in form of textbook. The textbook consisted of eight units in which each unit applied different reading strategies, such as skimming, scanning, guesing, activating schemata, summarizing, higlighting, and semantic mapping. The activity in each unit is divided into three parts. They are vocabulary enrichment, reading passage, and reading compre.